Does Melatonin Enhance Twin Lamb Survival in Commercial Merino Flocks in Australia? - Alyce M. Lowe; David O. Kleemann; Jennifer M. Kelly; Andrew N. Thompson; Jarryd Krog; William H. E. J. van Wettere; Alice C. Weaver (Animals)
In research flocks, supplementing pregnant ewes with melatonin has been shown to be a novel approach to ameliorate parturient neurological damage and improve twin lamb survival. This study investigated the commercial applicability of melatonin supplementation for Merino flocks managed under extensive grazing conditions. Multiparous twin-bearing ewes were implanted with one melatonin implant (18 mg, Regulin®) each on two properties in South Australia and one in Western Australia (n = 585) at a median 79 days of gestation, with control ewes not implanted (n = 586). Ewes were managed as per standard protocols for each property. Lambs and ewes were counted at tail docking and weaning, and the lambs were weighed at weaning. Lamb survival was not influenced by melatonin treatment at either tail docking (p = 0.327) or weaning (p = 0.546). Across all sites, lamb survival at weaning for control and melatonin treatments was 74.7% and 74.0%, respectively, with lamb weaning weight of 27.2 ± 0.1 kg and 26.8 ± 0.1 kg (p = 0.020). These results indicate that supplementing twin-bearing Merino ewes with melatonin during mid-gestation was not a practical strategy to increase either lamb survival or weaning weight on commercial farms.